Acupuncture attenuates experimental autoimmune thyroiditis by modulating intestinal microbiota and palmitic acid metabolism - Li, Huimin; Qi, Fengjun; Li, Dan; Fan, Yun; Liu, Jianmin; Li, Cui; Chen, Jun; Wu, Xinyue; Zhang, Xiaojing; Xu, Fei (Frontiers in Immunology, 2025)
IntroductionAutoimmune thyroiditis (AIT) is a common and chronic autoimmune disease. Recent evidence indicates that serum metabolites and dysbiosis of the intestinal microbiota are associated with AIT, with the underlying mechanism involving the apoptosis of thyroid follicular epithelial cells. Acupuncture, a traditional Chinese therapy, has demonstrated potential regulatory effects on various immune-related diseases. Clinical symptoms in AIT patients have shown improvement following acupuncture intervention. However, the mechanism underlying its therapeutic effects remain poorly understood.MethodsIn this study, we investigated the mechanisms of acupuncture (Acu) treatment in rats with established experimental autoimmune thyroiditis (EAT) and evaluated the relationship between microbiota and serum metabolites after Acu treatment. After six weeks of acupuncture and Selenium yeast intervention (used as a positive control), enzyme-linked immunosorbent assay was used to employed to assess the expressions of serum thyroid function and inflammatory markers. Pathological changes in the thyroid gland were observed using hematoxylin-eosin staining and electron microscopy. Thyroid apoptosis was evaluated through TUNEL staining, immunohistochemistry and Western blot analysis. Additionally, changes in intestinal microbiota and serum metabolic profile were analyzed by 16S ribosomal RNA (16S rRNA) sequencing and LC-MS metabolomics, aiming to identify potential therapeutic targets for acupuncture intervention in AIT.ResultsThe results revealed that Acu could effectively improve thyroid dysfunction and histopathological changes in EAT rats. Following Acu treatment, the content of B-cell lymphoma-2 (Bcl-2) increased, while the levels of Bax and the proportion of cleaved caspase-3 in thyroid tissue decreased. This may be associated with the amelioration of intestinal microbiota dysbiosis and metabolic disorders in EAT rats. Acu mitigated EAT-induced metabolic disorders by regulating the metabolism of palmitoleic acid, and adjusted intestinal microbiota dysbiosis by increasing the abundance of Prevotella. Furthermore, the microbiota (Prevotella) and metabolites (Cyclohexanecarboxylic acid, Tetradecanedioic acid) may serve as co-targets for both Acu and Selenium yeast treatment in EAT.DiscussionAcu improves the apoptosis of thyroid follicular epithelial cells in rats in EAT model, and its mechanism may be related to intestinal microbiota and metabolism.